2021
DOI: 10.1681/asn.2020101537
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Soluble ACE2 Variant with Prolonged Duration of Action Neutralizes SARS-CoV-2 Infection in Human Kidney Organoids

Abstract: BackgroundThere is an urgent need for approaches to prevent and treat SARS-CoV-2 infection. Administration of soluble ACE2 protein acting as a decoy to bind to SARS-CoV-2 should limit viral uptake mediated by binding to membrane-bound full-length ACE2, and further therapeutic benefit should result from ensuring enzymatic ACE2 activity to affected organs in patients with COVID-19.MethodsA short variant of human soluble ACE2 protein consisting of 618 amino acids (hACE2 1–618) was generated and fused with an albu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
118
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(128 citation statements)
references
References 49 publications
(84 reference statements)
6
118
1
1
Order By: Relevance
“…Therefore, the direct blockade of ACE2, by removing the physiological brakes on the angiotensin system, could have detrimental effects on COVID-19 disease. For these reasons, an alternative strategy to inhibit the interaction of SARS-CoV-2 with ACE2 could be the administration of recombinant soluble ACE2 as a decoy receptor, which has been previously tested in small clinical trials in acute respiratory distress syndrome [ 39 ] and is now being explored in COVID-19 disease [ 40 42 ]. However, the level of circulating ACE2 does not necessarily reflect the expression of ACE2 in the plasma membrane of host cells.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the direct blockade of ACE2, by removing the physiological brakes on the angiotensin system, could have detrimental effects on COVID-19 disease. For these reasons, an alternative strategy to inhibit the interaction of SARS-CoV-2 with ACE2 could be the administration of recombinant soluble ACE2 as a decoy receptor, which has been previously tested in small clinical trials in acute respiratory distress syndrome [ 39 ] and is now being explored in COVID-19 disease [ 40 42 ]. However, the level of circulating ACE2 does not necessarily reflect the expression of ACE2 in the plasma membrane of host cells.…”
Section: Discussionmentioning
confidence: 99%
“…Different engineered variants of human recombinant soluble ACE2 (hrACE2), were reported to significantly inhibit SARS-CoV-2 infection in vitro and causing sustained viral entry blockade upon engagement of hrACE2 with the RBD in SARS-CoV-2 S protein with high affinity [79][80][81]. This is a potentially powerful treatment against SARS-CoV-2 VOCs as it can exploit the increase S-protein host receptor-binding affinity caused by S-mutations, toward increasing S-protein affinity to hrACE2.…”
Section: S1 Rbd Targeted Therapymentioning
confidence: 99%
“…Nevertheless, it has been demonstrated that the human recombinant sACE2 tends to decrease angiotensin II and concomitantly increases Ang 1–7 [ 58 , 59 , 60 ]. Furthermore, the generated soluble variant of ACE2 serves as a decoy receptor and binds to the spike proteins of SARS-CoV-2 virion in order to limit the virus uptake by membrane-bound ACE2 receptors [ 61 ]. These issues further interrogate whether the circulating native sACE2 could exert a protection against angiotensin II mediated cardiac dysfunction or could it effectively bind to SARS-CoV-2 spike protein as the patients with comorbid conditions, including heart failure or CAD are more vulnerable to the SARS-CoV-2 mediated severity, despite elevated sACE2 levels in their circulation.…”
Section: Sars-cov-2 and Its Receptors In Cardiac Pathophysiologymentioning
confidence: 99%